USING TASK-BASED LEARNING METHOD TO ENHANCE STUDENTS’ LITERAL READING COMPREHENSION - AS, Nurul Dwi Pratiwi; Sakkir, Geminastiti; G, Hasriani (Universitas Negeri Makassar, 2025)
The objective of this study was to ascertain whether or not the task-based learning method can enhance students' inferential reading comprehension. A pre-experimental design with pre-test and post-test was employed in this study, which was conducted with all students in the 11th grade as the population. The sample consisted of 36 students from class 11.2 at UPT SMAN 5 Pinrang. The data were collected via an inferential reading comprehension test and subsequently analyzed using a paired sample t-test. The findings indicated a statistically significant enhancement in students' inferential reading comprehension, as evidenced by a probability value of less than 0.001, which was below the 0.05 significance threshold. The t-value (14.244) exceeded the t-table value (2.03), thereby confirming the acceptance of the alternative hypothesis (Ha). Additionally, the N-Gain value was classified as high (>0.70), providing further evidence of the effectiveness of this method. These findings demonstrate that the task-based learning method is an effective method to significantly enhance students' inferential reading comprehension. Consequently, this method can be a viable alternative teaching strategy for enhancing reading comprehension within similar educational contexts.